A Theoretical Study on the Degenerate Cope Rearrangement of Hypostrophene Using the RRKM Theory and Topological Approaches. Issue 7 (15th February 2021) - Khojandi, Mahya; Zahedi, Ehsan; Seif, Ahmad; Taghvamanesh, Afshin; Karimkhani, Mehrnoosh
Abstract: The CBS‐APNO and CBS‐QB3 model chemistries have been used to study the temperature‐ and pressure‐dependent kinetics of degenerate Cope rearrangement of hypostrophene. The rate constants are calculated by means of RRKM theory and corrected by the Wigner tunneling correction. The high‐ and low‐pressure limits of the rate constants reveal that the TST is valid to estimate the rate constant at 1 bar and the reaction in the bimolecular region cannot be observed experimentally. The estimated rate constant and activation energy at 1 bar and 308 K are 10 −2  s −1 and 89 kJ.mol −1, respectively, such that the homoaromatic transition structure is stabilized by 85 kJ.mol −1 because of the interactions between the allyl moieties. Evolution of chemical events along the reaction has been analyzed by the BET together with the NCI and AIM topological approaches at the B3LYP with 6‐311G( d, p ) basis set. The progress of reaction was monitored by five SSDs and controlled by the succession of catastrophes C † [F]2 TS [F † ]2 C. The sequential chemical events consist of homolytic rupture of C−C bond and formation of pseudoradical centers on carbon atoms, disappearance of the generated pseudoradical centers, formation of new pseudoradical centers on two carbon, and formation of new C−C single bond through the C− to −C coupling of the generated pseudoradical centers. The NCI and AIM analyses have been performed to study the nature of the interaction in the regions where bond rupture/formation occur. Abstract : The kinetics and molecular mechanism of the gas phase degenerate Cope rearrangement of hypostrophene have been studied by means of RRKM theory and topological approaches. The reaction proceeds via a homoaromatic transition structure with an activation energy of 89 kJ.mol −1 and may be represented by the succession of C † [F]2 TS [F † ]2 C catastrophes.